The Role of Leadership in Employee Performance - Firmansyah, Andrie (Journal of Management, 2024)
This study aims to examine the influence of leadership on employee performance at PT Anuta Karya Prima. This study found that Leadership There is a significant positive influence of Leadership on employee performance, with a significance value of 0.00. The T coefficient analysis shows a value of 3.330 which is greater than the T table value of 1.550, indicating that Leadership has a significant effect on employee performance. There is no significant effect of job satisfaction on employee performance, with a significance value of 0.472. The T coefficient analysis shows a value of 0.705 which is smaller than the T table value of 1.550, indicating that job satisfaction does not have a significant effect on employee performance. Leadership Style, has a significant positive effect on leadership style on employee performance, with a significance value of 0.014. The results of the T coefficient analysis show a value of 2.499 which is greater than the T table value of 1.550 indicating that leadership style has a significant effect on employee performance.